2016
DOI: 10.1016/j.jad.2016.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive functioning in individuals with bipolar disorder and their healthy siblings: A preliminary study

Abstract: Background Cognitive deficits have been consistently reported in individuals with bipolar disorder (BD). The cognitive profile of siblings of individuals with BD is, however, less clearly established possibly due to the heterogeneity of neuropsychological measures used in previous studies. The aim of this exploratory study was to assess the cognitive function of siblings of individuals with BD and compare it with that of their first-degree relatives suffering with BD, and healthy controls (HC) using the Cambri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 58 publications
1
6
1
2
Order By: Relevance
“…The enhanced function in some of the domains in our sample differs from the deficits that characterize most earlier work on BPD (Bauer et al, 2016; Cardenas et al, 2016; Lee et al, 2014; Sharma et al, 2016), and may reflect findings from earlier studies that people with BPD may actually have superior functioning in some cognitive domains, and higher IQ, school performance, and social functioning prior to onset of BPD (Demjaha et al, 2012), even in childhood (Cannon et al, 2002; Koenen et al, 2009; MacCabe et al, 2010). Of particular relevance to our study, the line orientation task has been shown to index greater functional life skills performance (for basic financial tasks) (Allen et al, 2015), so our finding of greater accuracy in visuospatial function could actually have broader functional implications.…”
Section: Discussioncontrasting
confidence: 56%
“…The enhanced function in some of the domains in our sample differs from the deficits that characterize most earlier work on BPD (Bauer et al, 2016; Cardenas et al, 2016; Lee et al, 2014; Sharma et al, 2016), and may reflect findings from earlier studies that people with BPD may actually have superior functioning in some cognitive domains, and higher IQ, school performance, and social functioning prior to onset of BPD (Demjaha et al, 2012), even in childhood (Cannon et al, 2002; Koenen et al, 2009; MacCabe et al, 2010). Of particular relevance to our study, the line orientation task has been shown to index greater functional life skills performance (for basic financial tasks) (Allen et al, 2015), so our finding of greater accuracy in visuospatial function could actually have broader functional implications.…”
Section: Discussioncontrasting
confidence: 56%
“…Although the study of cognition in relatives of individuals with BD is not new, findings in this group are still somewhat inconsistent (Balanza-Martinez et al, 2008;Cardenas et al, 2016;Hasler et al, 2006). For example, current work suggests that endophenotypic markers of genetic vulnerability for BD may be represented by deficits in verbal memory (Arts et al, 2008;Balanza-Martinez et al, 2008;Cardenas et al, 2016;Kieseppä et al, 2005;Kulkarni et al, 2010;McIntosh et al, 2005) and selective deficits in aspects of executive function and sustained attention (Arts et al, 2008;Bauer et al, 2016;Bora et al, 2008;Clark et al, 2005b;Ferrier et al, 2004a;Glahn et al, 2004;Nehra et al, 2006;Trivedi et al, 2008;Zalla et al, 2004), since FDRs have shown impairments on these domains relative to HCs. Speed of processing and verbal working memory deficits also seem to be related to genetic risk for BD, yet results on these domains are mixed, with some studies evidencing deficits in FDRs and others not (Antila et al, 2007b;Cardenas et al, 2016;Daban et al, 2012;Nehra et al, 2006;Pierson et al, 2000).…”
mentioning
confidence: 91%
“…Our conclusions are largely consistent with other family risk studies that employed broader inclusion criteria (e.g., studies that include in their risk group a range of first-degree relatives like siblings, parents, and offspring). Using this broader inclusion criteria, there were several studies that failed to find FSIQ differences between patients with bipolar disorder, their first-degree relatives, and healthy controls [ 61 , 62 , 63 , 64 , 65 , 66 ], with some noted exceptions showing lower FSIQ in relatives of patients with BD (e.g., [ 67 , 68 ]. There were several family risk studies that also found lower PIQ or a larger discrepancy between VIQ and PIQ for those at family risk for BD (e.g., [ 64 , 68 ].…”
Section: Discussionmentioning
confidence: 99%